Titanium: Material Features for its Use in Orthodontics (2016)
Introduction: Titanium and its alloys have been long used in Medicine and Odontology due to their numerous properties, among them their high resistance to corro sion and outstanding biocompatibility. In the case of orthodontics, titanium and its alloys have a relatively short history, but its use has been increased during the last years, due to its excellent mechanical properties, like its design-in memory effect and super-elasticity, which provide this material with extraordinary biomechanical performance, especially in the case of orthodontic wire, which is highly searched for in the area of orthodontics. Objective: To examine the history of titanium in orthodontics, its main characteristics, its physical and mechanical properties and its use within a spectrum of orthodontic materials available in the market. Conclusion: Titanium alloys are used in conjunction with other elements (nickel, molybdenum and copper, amongst others) that leverage the titanium’s properties and allow the operation of its clinical qualities.